2008
DOI: 10.1074/jbc.m707159200
|View full text |Cite
|
Sign up to set email alerts
|

CaV3.2 T-type Calcium Channels Are Involved in Calcium-dependent Secretion of Neuroendocrine Prostate Cancer Cells

Abstract: Because prostate cancer is, in its early stages, an androgen-dependent pathology, treatments aiming at decreasing testosterone plasma concentration have been developed for many years now. However, a significant proportion of patients suffer a relapse after a few years of hormone therapy. The androgenindependent stage of prostate cancer has been shown to be associated with the development of neuroendocrine differentiation. We previously demonstrated that neuroendocrine prostate cancer cells derived from LNCaP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 48 publications
4
61
0
1
Order By: Relevance
“…Indeed, PAP expression is increased in prostate bone metastasis and PAP may participate in the osteoblastic phase of the metastasis development [115]. Moreover, we have shown that the expression of Cav3.2 channels is correlated with the expression of serotonin [86], a neurotransmitter stimulating the proliferation and migration of prostate cancer cell lines [116]. Furthermore, we have shown that Cav3.2 expression correlates with CgA expression [86].…”
Section: Ne Differentiation In Cancer Progression-perspectives On Thementioning
confidence: 68%
See 3 more Smart Citations
“…Indeed, PAP expression is increased in prostate bone metastasis and PAP may participate in the osteoblastic phase of the metastasis development [115]. Moreover, we have shown that the expression of Cav3.2 channels is correlated with the expression of serotonin [86], a neurotransmitter stimulating the proliferation and migration of prostate cancer cell lines [116]. Furthermore, we have shown that Cav3.2 expression correlates with CgA expression [86].…”
Section: Ne Differentiation In Cancer Progression-perspectives On Thementioning
confidence: 68%
“…Their role in cell proliferation may be due to the fact that enhanced expression of T-type calcium channels (Cav3.1, Cav3.2 or Cav3.3) leads to increased secretion of tumorigenic factors by NE cells. As we have previously shown, PAP synthesis and release are enhanced by Cav3.2 channels in LNCaP cells [86]. In addition, the secreted form of PAP may play an important role in the development of prostate tumour metastasis.…”
Section: Ne Differentiation In Cancer Progression-perspectives On Thementioning
confidence: 76%
See 2 more Smart Citations
“…Novel splice variants of T-type VACC are commonly detected in human glioma, breast, ovarian, prostate colon and esophageal cancer cells [36][37][38][39][40] . For example, the Cav3.1a transcripts predominate in the normal adult brain, but human glioma and glioma cell lines contain Cav3.1bc as predominant splice and Cav3.1ac as a novel splice variant, which is absent in normal brain [36][37][38][39][40] . 45 .…”
Section: Introductionmentioning
confidence: 99%